2019
DOI: 10.3390/su11174799
|View full text |Cite
|
Sign up to set email alerts
|

Improving Phosphorus Use Efficiency and Optimizing Phosphorus Application Rates for Maize in the Northeast Plain of China for Sustainable Agriculture

Abstract: Optimizing the phosphorus (P) application rate can increase grain yield while reducing both cost and environmental impact. However, optimal P rates vary substantially when different targets such as maximum yield or maximum economic benefit are considered. The present study used field experiment conducted at 36 experiments sites for maize to determine the impact of P application levels on grain yield, plant P uptake, and P agronomy efficiency (AEP), P-derived yield benefits and private profitability, and to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…Agronomic efficiency of the P fertilizer (AEP, kg grain kg -1 P) or an increased grain yield per kg P applied was calculated [36] as follows AEP kg=kg ð Þ ¼ ðGrain in fertilized treatment À Grain without fertilizationÞ Fertilizer P applied…”
Section: Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Agronomic efficiency of the P fertilizer (AEP, kg grain kg -1 P) or an increased grain yield per kg P applied was calculated [36] as follows AEP kg=kg ð Þ ¼ ðGrain in fertilized treatment À Grain without fertilizationÞ Fertilizer P applied…”
Section: Calculationmentioning
confidence: 99%
“…The AEP or increased yield per unit of P applied represents the direct production impacts of an applied fertilizer [55], and is often used to evaluate optimum P management practices [36]. The AEP values of PAPRs were comparable to TSP and SSP in both NAS-D and Ramongo, and CBs showed a consistent performance in the NAS-D because of the reasons mentioned above (Fig 6).…”
Section: Agronomic Efficiency Of P Fertilizers (Aep)mentioning
confidence: 99%
“…Currently, the functional models used include one-dimensional quadratic model, linear platform model, exponential model and square root model, etc. The optimal fertilizer amount obtained has the advantage of high accuracy, and the economic fertilizer application amount, upper limit and lower limit of fertilization can be calculated (Chen et al 2014;Rosen et al 2014;Jiang et al 2019). In our study, with the increased of experimental years, cumulative effects of fertilizer P application on soil P availability and crop yield were supposed to be strengthened, resulting in the yield level decline at zero P supply, a yearly-increased yield gap between low and high P supply, and high P surplus at high P application rate (Liao et al 2021;Zhou et al 2023).…”
Section: Synergies Between Intercropping and Optimized P Managementmentioning
confidence: 99%
“…Starting from the fact of grain production in China, some scholars found that the insufficient utilization rate of grain production factors and the lack of scientific input led to unnecessary waste [10]. Those scholars also believe that optimizing grain production factors and improving the input efficiency of production factors are conducive to the overall improvement of grain production efficiency [11]. Most of these scholars conduct research from factors such as chemical fertilizers, labor, and land.…”
Section: Introductionmentioning
confidence: 99%